Killing Congress : assassinations, attempted assassinations and other violence against members of Congress - Marion, Nancy E. (Lexington Books, 2014)
Killing Congress: Assassinations, Attempted Assassinations, and other Violence Enacted on Members of the U.S. Congress analyzes all assassinations, attempted assassinations, and other violent acts carried out on members of Congress. Each chapter focuses on a particular incident, describing the events, the people involved, and the consequences of the violence.